International franchising: strategies for building bridges between Asia and North America / Andrew J. Sherman, Esq. (Faculty of Business and Management ; UiTM Press, 1996)
The author discusses franchising as a currently popular expansion strategy for companies around the world. In light of this, the paper urges future members of the international franchising community to take a careful and responsible approach to the development of franchising programs. This is looked at from the viewpoint of the basics of franchising and how it can be used to build international trade lingkages between Asia and North America in particular.